2017
DOI: 10.1021/acsami.7b12313
|View full text |Cite
|
Sign up to set email alerts
|

Dense Vertically Aligned Copper Nanowire Composites as High Performance Thermal Interface Materials

Abstract: Thermal interface materials (TIMs) are essential for managing heat in modern electronics, and nanocomposite TIMs can offer critical improvements. Here, we demonstrate thermally conductive, mechanically compliant TIMs based on dense, vertically aligned copper nanowires (CuNWs) embedded into polymer matrices. We evaluate the thermal and mechanical characteristics of 20-25% dense CuNW arrays with and without polydimethylsiloxane infiltration. The thermal resistance achieved is below 5 mm K W, over an order of mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 39 publications
0
38
0
1
Order By: Relevance
“…To analyze and predict the pressure‐dependent thermal characteristics of BPCu/PDMS IPCs, pressure‐inverse functional form was adopted, and the relation between measured R ″ total and applied pressure could be expressed as: R ″ total = CP –1 + Y , where C represents the fitting parameter, P was the applied pressure, and Y was the equation offset in the y ‐direction . [ 24 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze and predict the pressure‐dependent thermal characteristics of BPCu/PDMS IPCs, pressure‐inverse functional form was adopted, and the relation between measured R ″ total and applied pressure could be expressed as: R ″ total = CP –1 + Y , where C represents the fitting parameter, P was the applied pressure, and Y was the equation offset in the y ‐direction . [ 24 ]…”
Section: Methodsmentioning
confidence: 99%
“…The use of continuous monolithic structure minimizes filler‐filler contact resistances, enabling a higher thermal conductivity. [ 23–25 ] The monolithic structures are often fabricated by backfilling the vacancies of a sacrificial template with a desired structural material, the structure with inverse‐morphology of the template is then formed. After the formation of the structural material, sacrificial templates are then typically etched or dissolved by using suitable chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is to enhance the intrinsic thermal conductivity of the polymers by the alignment of the polymer chains [4][5][6][7], but the high cost and complicated process are two major barriers for the large-scale application of this method. Besides engineering the structure and morphology of the polymer itself, another effective approach to enhance the thermal conductivity of the material is to incorporate into the polymer matrix a proportion of thermally conductive fillers, such as metals [8][9][10], ceramics [11,12], carbonbased materials [13] and their hybrids [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al reduced TCR using a TIM that synthesized aligned carbon nanotubes 9 (CNTs) on both sides of a thin copper foil. It has been reported that the [10][11][12] TCR is reduced by filling the TIM between the solid-solid interfaces. The heat transfer capacity between the rough solid-solid interface can be represented by the total TCR, which is mainly composed of two part: [13][14][15] (1) the bulk resistance(R ), (2) the boundary resistance(R ).…”
Section: Introductionmentioning
confidence: 99%